Determinants of Work Fatigue in Inpatient Nurses at RSI Siti Hajar Sidoarjo - Fisilmi Kaffah; Nafilatul Fitri; Fresvian Jenrivo; Rizki Mustika Riswari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Nurses are an important part of patient care so they are often required to provide optimal service which sometimes causes fatigue. With different individual characteristics of each worker such as age and physical condition of workers and job characteristics such as length of service and duration of work, it is possible to experience fatigue at different levels of fatigue. Objective: To determine the relationship between age, work period, and work shifts with work fatigue in inpatient nurses at RSI Siti Hajar Sidoarjo and identify the relationship between age with work fatigue, work period with work fatigue, work shifts with work fatigue in inpatient nurses at RSI Siti Hajar Sidoarjo. Method: This type of research is quantitative with random sampling technique. Data collectin was carried out with IFRC (Industrial Fatigue Research Committee) questionnaire instrument on 125 inpatient nurses at RSI Siti Hajar Sidoarjo. The bivariate analysis process is carried out by testing the data with the SPSS program using the Spearman Rank Correlation test. Result: The majority of inpatient nurses who have the potential to work fatigue are ?35 years old, had worked for ?5 years, working on the morning shift, experienced low fatigue and the majority of nurses felt thirsty, wanted to lay down after work, often yawned, sleepy, and tired all over. Based on the hypothesis test, between age and fatigue was obtained sig. 0.002 < 0.05, between tenure and fatigue obtained sig. 0.001 < 0.05, and between work shifts and work fatigue obtained sig. 0.032 < 0.05. Conclusion: There is a relationship between age, length of service, work shifts with work fatigue in inpatient nurses at RSI Siti Hajar Sidoarjo.